2017
DOI: 10.1038/srep40084
|View full text |Cite
|
Sign up to set email alerts
|

A new method for assessing the risk of infectious disease outbreak

Abstract: Over the past few years, emergent threats posed by infectious diseases and bioterrorism have become public health concerns that have increased the need for prompt disease outbreak warnings. In most of the existing disease surveillance systems, disease outbreak risk is assessed by the detection of disease outbreaks. However, this is a retrospective approach that impacts the timeliness of the warning. Some disease surveillance systems can predict the probabilities of infectious disease outbreaks in advance by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
1
29
0
3
Order By: Relevance
“…The expert knowledge method builds a network according to experts' comments and the results of literature reviews, while the network structure learning algorithm is based on the independence test proposed by Cheng and Greiner (1999). The network structure learning algorithm has three phases: drafting, thickening, and thinning (Liao et al 2017). In the first phase, the algorithm computes the mutual information of each pair of nodes as a measure of closeness, and it creates a draft based on this information.…”
Section: Building the Bbn Constructmentioning
confidence: 99%
“…The expert knowledge method builds a network according to experts' comments and the results of literature reviews, while the network structure learning algorithm is based on the independence test proposed by Cheng and Greiner (1999). The network structure learning algorithm has three phases: drafting, thickening, and thinning (Liao et al 2017). In the first phase, the algorithm computes the mutual information of each pair of nodes as a measure of closeness, and it creates a draft based on this information.…”
Section: Building the Bbn Constructmentioning
confidence: 99%
“…To our knowledge, no other study has been conducted on the performance of BODA. However, other algorithms using the Bayesian framework were used to detect outbreaks in various studies, most of which showed good performance (Garcia, Christen, & Capistran, 2015; Liao, Xu, Wang, & Liu, 2017; Texier et al., 2016, 2019). The BODA model has two advantages over traditional models, one using the Bayesian framework, which also uses the prior distribution to calculate the alarm threshold.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies related to machine learning modelling of infectious disease have been conducted on unsupervised analysis of several infectious diseases (PeterIdowu et al, 2013),measles outbreak prediction (Liao et al, 2017), dengue outbreak prediction (Rahmawati & Huang, 2016) and dengue infection risk (Fathima & Hundewale, 2012). Our prior work found that decision tree and Naive Bayes are among the techniques commonly used for disease risk prediction (Ahmad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%